Studi Komparatif Pemikiran Tasawuf al-Gazālī dan Ibn Taimiyah - Lalu Supriadi (Ulumuna, 2013)
Al-Gazālī plays an important role in purifying Sufism and directing it into the right path of Islam. Prior to his time, many people misunderstood Sufism. While some of them were concerned only with sufi theories but lost its practices, some others simply practiced Sufism without sufficient knowledge. In his time, where splits of religious sects and disintegration spread among Muslims, he emerged to offer his notion that integrates Sufi concepts of intuition, knowledge and spiritual path to achieve the highest objective of happiness. He himself reached these sufi paths through several stages in his life and spirituality. Meanwhile Ibn Taymiyya acknowledges the validity of experimental sufi but encourages a method of external examination, namely the basic teachings of Islam, to examine the validity of Sufism. According to him, Sufism is a form of religious expressions that must be built on the Qur’an and Sunna and has to refer to the practices of the Companions.